Práticas urbanas criativas: estudo, análise e impacto de ações táticas no espaço público paulistano - Bortolozzo, Carolina Vittória Ortenzi (2018)
The ephemeral condition of contemporaneity, the fluidity of interpersonal relations, the emphasis on urban design and the presence of gaps in urban planning contributed to the suppression of the human scale of the urban context, thus providing a scenario of physical and social transformations. The degradation, underutilization and abandonment of urban areas make it impossible for public spaces to exercise their primary function of inducing vitality, exchanges of experience and social interaction among people. The main objective of the research is to explore and consider the relevance of the application of creative urban practices in the current urban context, through the study of the impacts of these interventions in public spaces, mainly through collective engagement. In order to prove the real benefits and positive impacts of creative practices in public spaces, three programs were implemented in the metropolitan area of São Paulo (Centro Aberto, “A Batata precisa de Você” and Inova Cajamar), which enabled the transformation and activation of the where they were inserted, improving social indexes and creating new forms of use. Tactical actions appear as a mitigating tool for this process of urban deterioration, based on a more inclusive and dialectical approach to urban planning. This concept is challenged to promote new urban dynamics through, in principle, ephemeral, low-cost and highly flexible initiatives, which can then be transformed into concrete actions. Therefore, encouraging the implementation of certain initiatives, practices and interventions in urban space is an essential tool to combat the extinction of urban life and the gradual decay of public spaces.